The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1975
DOI: 10.1017/s0022112075001644
|View full text |Cite
|
Sign up to set email alerts
|

Viscous incompressible flow between concentric rotating spheres. Part 3. Linear stability and experiments

Abstract: The stability of flow of a viscous incompressible fluid contained between a stationary outer sphere and rotating inner sphere is studied theoretically and experimentally. Previous theoretical results concerning the basic laminar flow (part 1) are compared with experimental results. Small and large Reynolds number results are compared with Stokes-flow and boundary-layer solutions. The effect of the radius ratio of the two spheres is demonstrated. A linearized theory of stability for the laminar flow is formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
0

Year Published

1981
1981
2016
2016

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 75 publications
(43 citation statements)
references
References 9 publications
3
39
0
Order By: Relevance
“…Contour plots of the stream function for Re = 5000 are given in Figure 4.4. Our results are consistent with the flow visualization patterns obtained from experiments by Munson and Menguturk [9] as well as those of Wimmer [16].…”
Section: Resultssupporting
confidence: 92%
“…Contour plots of the stream function for Re = 5000 are given in Figure 4.4. Our results are consistent with the flow visualization patterns obtained from experiments by Munson and Menguturk [9] as well as those of Wimmer [16].…”
Section: Resultssupporting
confidence: 92%
“…For higher Re, there is a transition to an m = 2 mode. It is numerically expensive to conduct simulations at higher Reynolds numbers, but it is expected that successive bifurcations involving higher azimuthal wavenumbers eventually yield a turbulent state [28]. It has been recently shown that these non-axisymmetric instabilities can trigger dynamo action, but only when P m > 1 [29], which will not be considered here.…”
Section: Comparison With Experiments: Axial Field and Outer Spherementioning
confidence: 99%
“…Wimmer [12] showed that the flow modes could be produced by different acceleration histories of the inner sphere. Another study on torque measurements as a function of flow regimes was done by Menguturk and Munson [3]. They found a good agreement between the experiment and perturbation theory for narrow gap values.…”
Section: Nomenclaturementioning
confidence: 84%
“…Kinematic viscosity (m 2 s −1 ) θ i Angle measured from the sphere axis (°) S Wall velocity gradient (s −1 ) s ′ Fluctuation intensity of S (s −1 ) Tc 1 Critical value of start-up of Taylor vortices Tc 2 Critical value of spiral mode Tc 3 Onset of spiral mode & wavy mode Tc 4 Critical value of spiral wavy mode Tc 5 Critical value of azimuthal waves Tc 6 The near-turbulence regime Tc 7 Onset of chaos Tc 8 Developed turbulence…”
Section: Nomenclaturementioning
confidence: 99%